1996
DOI: 10.1097/00001648-199607000-00006
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Risk Factors for Preterm Labor and Term Small-for-Gestational-Age Birth

Abstract: This study estimates the effects of 23 factors on the prevalence of premature labor and fetal growth retardation across the entire birthweight spectrum. We studied risk factors for premature labor within the domain of babies of appropriate size for their gestational age (N = 9,490). We also studied risk factors for fetal growth retardation among babies born at term (N = 10,889). Preterm labor was associated independently with young maternal age, low pre-pregnant weight, low weekly weight gain, nulliparity, pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
109
1
7

Year Published

2000
2000
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 193 publications
(135 citation statements)
references
References 11 publications
18
109
1
7
Order By: Relevance
“…However, our data are inconsistent with findings of studies that have not found a significant association between cannabis use in pregnancy and birth outcomes (13,14,16,18). The existing discrepancy between the findings might be due to the difference in the study design and assessment of cannabis use (e.g., retrospective vs. prospective) (14) or level of adjustment for confounders (13,16). Using a large routinely collected data set, our study suggests a significant effect of in utero exposure to cannabis on the birth outcomes examined independent of sociodemographic background and use of other substances.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…However, our data are inconsistent with findings of studies that have not found a significant association between cannabis use in pregnancy and birth outcomes (13,14,16,18). The existing discrepancy between the findings might be due to the difference in the study design and assessment of cannabis use (e.g., retrospective vs. prospective) (14) or level of adjustment for confounders (13,16). Using a large routinely collected data set, our study suggests a significant effect of in utero exposure to cannabis on the birth outcomes examined independent of sociodemographic background and use of other substances.…”
Section: Discussioncontrasting
confidence: 99%
“…The findings of this study are consistent with previous research, which has suggested that smoking cannabis during pregnancy may lead to lower birth weight (6-9), increased rate of premature birth (7), and shorter birth length (11,12). However, our data are inconsistent with findings of studies that have not found a significant association between cannabis use in pregnancy and birth outcomes (13,14,16,18). The existing discrepancy between the findings might be due to the difference in the study design and assessment of cannabis use (e.g., retrospective vs. prospective) (14) or level of adjustment for confounders (13,16).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…Saúde Pública, Rio de Janeiro, 16(1):83-94, jan-mar, 2000 Introdução Apesar dos avanços alcançados pelos programas de investigação sobre os fatores de risco da prematuridade, a maioria dos nascimentos prematuros ainda não tem fisiopatogênese conhecida (Kramer, 1987;Kramer et al, 1988;Mavalankar et al, 1992;Fortier et al, 1995;Hedegaard et al, 1996;Lang et al, 1996). Dentre as principais dificuldades dessa linha de pesquisa, destaca-se a falta de consenso com relação aos indicadores e medidas usados para aferir alguns de seus potenciais fatores de risco e à estratégia padrão utilizada para seu diagnósti-co (Dunn, 1985;Henriksen et al, 1995).…”
Section: Artigo Articleunclassified
“…Alguns trabalhos mostraram um maior número de nascimentos prematuros entre as gestantes adolescentes 56,89,103,120,127,137 , enquanto outros autores concluíram que não houve um aumento do risco de prematuridade entre as mães adolescentes 49,57,72 .…”
Section: Variáveis Maternasunclassified